Primary Central Nervous System Lymphoma Revealed by 68Ga-FAPI and 18F-FDG PET/CT. (August 2021) - Zhang, Ying; Cai, Jiawei; Lin, Zefang; Yao, Shaobo; Miao, Weibing
Abstract : Abstract: A 67-year-old woman presented with left limb weakness, facial paralysis, and unsteady gait for 1 month. Brain MRI detected a mass in the right frontal lobe with prominent peritumoral edema, suggesting a malignant brain tumor. In 18 F-FDG PET/CT, the mass was very FDG avid, and 68 Ga-FAPI PET/CT showed the mass had heterogeneously mild to moderate increased uptake of the tracer. Histopathological examination after surgical resection of the mass confirmed the diagnosis of diffuse large B-cell lymphoma. The current case indicated the existence of fibrosis in the lymphoma lesion to some extent.